Papyrus - Ryan, Donald P. (The Biblical archaeologist, 1988)
Cyperus papyrus was one of the most versatile plants in antiquity. In addition to its being made into paper, it was used to construct boats, containers, and rope. It was also used medicinally, eaten, and burned for its aroma. And there's more.